PENGARUH LEMBAGA PENDIDIKAN ISLAM KEGIATAN MEANING FULL STUDI KEISLAMAN KURIKULUM BERBASIS CINTA PADA MADRASAH IBTIDAIYAH - Meti Friska; Suwandi; Ahmad Zainuri; Frika Fatimah Zahra (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study explores how Islamic educational institutions, meaningful learning strategies in Islamic subjects, and the application of a love-centered curriculum influence learning practices in Islamic elementary schools (Madrasah Ibtidaiyah). Using a literature review method, the research synthesizes insights from recent scholarly publications. The results indicate that Islamic educational institutions provide a foundational role in shaping students’ morality and spiritual growth through routine worship activities and the cultivation of a religious school atmosphere. Meaningful learning supports students in linking Islamic teachings with everyday situations, enabling deeper comprehension, while a love-driven curriculum encourages a compassionate and supportive classroom climate. Altogether, these elements substantially enhance students’ spiritual, emotional, and academic development.